The RNA M5C methyltransferase NSUN2 promotes progression of hepatocellular carcinoma by enhancing PKM2-mediated glycolysis - Qin Qi; Rui Zhong; Yan Huang; Yong Tang; Xiao-wen Zhang; Chang Liu; Chun-fang Gao; Lin Zhou; Jian Yu; Lu-yi Wu (Cell Death and Disease)
Abstract Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide. The 5-methylcytosine (m5C) RNA methyltransferase NSUN2 is involved in cell proliferation and metastasis and is upregulated in a variety of cancers. However, the biological function and regulatory mechanism of NSUN2-mediated m5C modification have not been well studied in HCC. Our results showed that NSUN2 is upregulated and associated with poor prognosis in HCC patients after hepatectomy. NSUN2 overexpression significantly promoted HCC growth and metastasis, whereas NSUN2 knockdown had the opposite effect. m5C RNA immunoprecipitation sequencing (m5C-RIP-Seq) revealed that m5C hypermethylation correlates with mRNA overexpression and that NSUN2-mediated m5C hypermethylation promotes metabolism in HCC patients. Mechanistically, our data revealed that PKM2, a terminal enzyme in the glycolytic pathway, is a downstream target of NSUN2-mediated m5C modification. Specifically, NSUN2 could stabilize PKM2 mRNA by increasing the m5C level of the m5C site C773 in the 3′-UTR of PKM2 mRNA. In addition, rescue assays revealed that NSUN2 promotes HCC glycolysis and progression by upregulating PKM2. In conclusion, this study revealed that NSUN2-mediated m5C modification promotes glycolysis and the progression of hepatocellular carcinoma by stabilizing PKM2 mRNA, and provides a potential prognostic factor and therapeutic target for HCC patients.